The role of parental communication in developing Muslim personality: an overview of parental acceptance –rejection theory / Aini Faezah Ramlan … [et al.] - Ramlan, Aini Faezah (2015)
Family communication is essential to create positive environment in a family. This type of communication involves on the interaction between the family members such as the parents with the children and vice versa. The study of family communication is attributed to the understanding towards the factor of social problems among the youths, conficts in marriage and other consequences of degrading in terms of human interpersonal communication. Parental communication is very essential in developing youth personality. Islam emphasizes the role of parents in nurturing their children as an asset for the ummah. Muslim personality is the source of goodness and constructive elements in the society. Positive interactive between parents and adolescents in families would lessen towards health risk behaviors behaviours that contribute to unintentional injuries, tobacco use, alcohol and other drug use, sexual behaviors that contribute to unintended pregnancy and others. However, nurturing children according to the Islamic values in modern-globalized environment is quite challenging. Family communication and interaction is lessen due to the increasing usage of technology. Research findings on deliquencies behaviors among Malay youths showed that family institutions have contributed to the increasing rate of social ills in societies (Azizi Yahya & Badrulzaman Baharom,(nd). This article will highlight the role of parental comunication in developing Muslim personality by reviewing Parental acceptance-Rejection theory. The conflict of parents in developing future ummah will be discussed by focusing their pattern of communication and level of acceptance and rejection towards their children in Muslim societies.